S154 Is there a role for IL-33 in the pathogenesis of pulmonary arterial hypertension?. (16th November 2010) - Shao, D; Perros, F; Humbert, M; Caramori, G; Price, L; Addcock, I; Wort, S
Abstract : Introduction and objectives: IL-33 is a 31KDa cytokine which is a member of the IL-1 family. It resides in the nucleus of endothelial and epithelial cells as a chromatin-associated factor in vivo. IL-33 is thought to be released from stressed or necrotic, but not apoptotic, endothelial or epithelial cells in response to cell injury or infection, acting as an endogenous 'alarmin', to alert the immune system of cell and tissue damage. IL-33 is then able to bind to its receptor (ST2) on immune cells, thereby stimulating immunoregulatory activity through induction of NF-κB and mitogen-activated protein kinases, as well as enhancing the production of the Th2 cytokines IL-5 and IL-13. There is increasing evidence that IL-33 may have a protective role in terms of endothelial integrity and function. As the pathogenesis of pulmonary arterial hypertension (PAH) is thought to involve endothelial cell dysfunction, we were interested to see whether there may be a role for IL-33 in this condition. Methods: RT-PCR for IL-33 was performed on human pulmonary arterial cells (HPAECs) derived from normal healthy controls and patients with idiopathic PAH. siRNA IL-33 knockdown was performed using smartpool duplexes on normal HPAECs. RT-PCR was then performed using QuantiTec primer assays. Results: IL-33 mRNA expression was decreased 2.1-fold in PAH patient samples (0.369±0.02, n=10) compared to controls (0.761±0.06, n=14) p<0.005. In normal human lung tissue, intense IL-33 staining was shown in the ECs nuclear in blood vessels. It is also worth to note that there was little or no IL-33 staining in non-ECs. siRNA knockdown IL-33 in HPAECs resulted in a 1.8±0.22, 1.3±0.13 and 1.4±0.20 (n=3) fold increase of mRNA IL-6, BMP-9 and ST2 mRNA, respectively; whereas RANTES, fractalkine and cathepsin-L mRNA was decreased by 1.5±0.03, 1.7±0.01 and 2.1±0.17 fold respectively (n=3) (Abstract S154 Figure 1 ). Conclusion: IL-33mayplay an important role in the pathogenesis of PAH through regulating the expression ofcytokines and chemokines known to be involved in vascular remodelling. In particular, it is of interest that Il-33 may regulate IL-6 production and ST2 which acts as an endogenous IL-33 inhibitor.